To determine the symmetry of the function \( f(x) \), we need to consider the definition of an even function. A function \( f(x) \) is even if it satisfies the condition \( f(-x) = f(x) \) for all \( x \) in the domain of \( f \).
Given the values from the table:
- \( f(-5) = 7 \) and \( f(5) \) is not provided, but we won't use this point for testing symmetry.
- \( f(-3) = 3 \) and \( f(3) = 3 \) → satisfies \( f(-3) = f(3) \)
- \( f(-1) = -2 \) and \( f(1) = -2 \) → satisfies \( f(-1) = f(1) \)
- \( f(0) = 1 \) (symmetric about the y-axis but only at x = 0)
Since \( f(-x) = f(x) \) holds true for the values provided (except for \( f(5) \)), we can conclude that the function \( f(x) \) indeed demonstrates even symmetry about the y-axis.
Thus, the correct statement is:
The graph of f(x) is symmetric about the y-axis.